Solutions To DE Problems

Download as pdf or txt
Download as pdf or txt
You are on page 1of 11

Separable DE Se"sinxdx =

-excosx
- (-Je cosXdx)
+

IBP
1) y(n(x)(n(y)dx +
xdy =
0
eX
u =
dr = cosXdX
y(n(x1(ntyldx xdy
+
+ - =
0 du =
e dxv = sinX
X
y(n(y)

(in)ax
Se"sinxdx -ecosx-[-(e"sinx-Jesinxx)]
Sy
=

+ =

=
=
ecosX +
esinx-Se"sinxdx
u InX
In y
=
u =

du +dX (Jesinxdx =
e"sinx-e"cosx)I
du
ty dy
=
=

2(gm =x +
In/my) =
c) [C =
e +
e(sinx-cosx)]2
-

C =
(n 2x + 2(n)(ny) C =
Ley + e
*
(sinx-cosx)

2)xy 2dx +
(xy y 2x 2)dy
+ - - =
0
4) =
xy 2 dx +
(xy y 2x 2)dy
+ - - =
0
PFD :

G
y(x + 1) 2(x + 1) & 2x 0


-
=

A(x 2) +Bx
Xy-
1
- 2)dy
-

2dx
1)(y St5 Sax
=
+
(x +
- =
0
=

(x + 1) A =
-

t
Gy (55)2

+
e X =
2

Sax +

Say - 1 =
-
A(X 2) + BX -

-
Judy- 2 Sy dy
u X+ 1
t
o
=

B
=
+ =

du =
dX

- arctan()
X 1
- (x) + x-2
=
n -

Sadu-Sdu
(C =

in)-arctan()]5
(C =
x + -

(n(x + 1) +
in(y) -

)y
Cy
=

y(x -
(n(x + 1) +
(n(y)) + 2
c =

55 (n)/)-arctan()
cy
=

y(x m)x1))+ + 2 5)(yz 1)dx + + (x +


1)dy =
0 ;

y(0) =
1

3) ex Y sinXdx
+
+
e3Ydy =
o 1)dx
xy + + (x + 1)dy
- =
0

-sinxdx
exeY + e2] dy =
0
(x2 + 1) (yz 1) +

eY
SS =
o

Jesinxdx +
Serdy- C =
arctanx +
arctany ; y(0) = 1

IBP :

u = e*dv = sinxdX
C tano tran
=

+
du dxv
arctany)
e =

Carctanx
=
cosX
-

it =
↑ +

Sud =

ur-Judu
Homogenous DE 3) sin() =
sin()
1) y
= [i =
sin() 1)
- +
since
+ -
Y(
X

+ =
-

r) +

X -1
& =+
=

= Ssinvdu f =

Sear =
-

((x) + c -

cosu + c =
(nXiv =

cos()
u = 3 (v
C (nx +
1) arctan(v)
=

+ + =
n

= 1
)(2x y 3)dx (x + +y + 3)dy 0
-
- - =

ev
.

[in)()" 1) In (x) arctan (# ) c] (2x y 3)dx ( 3)dy


+ x +
y 0
- -
- - -
=
+
2 + + =

C =

In) + In +
cat -
c (n(y2 x2) + +
Carctan()
9
=

c =

SMOX + "Terms in N wox" dy


2)
=y =

f(ex -

y
-

3)2x +
f( +y -

3) dy

2y
vX
y
+
=

c =
X 3x +
3y
xy
+
-

-
-

= r
-
5)(2x -

3y +
2)dx + 3(+X by - -

1)dy =
0

+ 2
3

2v
-v =
(2x -

3(2(2x 3y) 1]dy


3y
+ 2)dx + - -
= 0

22
3(2(2x 3y) 1] d- -
X

==
n = + 3

=--B
(3
(n(2v2 3) + + c =
(nxiv =

4
- e)

-
-

"

in
12 (*) +
3) -

1nX = c

C =

In/2my()
r
(5)
StarFax
C =
In
ar-
(15) =
/ x)
(Er -Ym(v) 2)52v
C
+ 2x
x
3y
= -
=

5x4 =
3x2 +
2y C =
(n(2x -

3y) + x +
by
Exact DE EDE :
"

(x-
c =

(y3(3x 2x +
y)x(x) Jody
+ +

-) (2x y 2yz 2xy)dx+ +


2y)dy 0
-
- =

c =

x3y3 + ax
y c =
x
y(xy 2) +

= 2x- ty +
2x = -

Ex X

4) (23x)ax +
[2y(n)) 3sing]dy + =
0
IF :

↑ -)
2x"
+y +x
2My
-

x2
2y
-

3X

e2)dx 2(2y)
= ziu =
2X
(x
-
= =
e

x2Y
e
*
x[(2x y -

2y 2xy)dx + + (x -

2y)dy =

0]
=

2y[(nu) (i)
GM 2xe-eye 2xek 2y[( * )(x
+ 32(5x) 5x2(x+
3))]
-

=
= +

V (X + 3)

=
= tye* 2xe2x
- *
2x e -
+ x

EDE :
EDE :

c =

(fxe Cy -2Jye (y)


* *
+
ody" syn +
3 fsinydy
=
C

PFD :

*
(x* y) & 0 2x 3
-
= =

c X
ye
-
=

1 = A(x 3) + +
(x" 1 =
3)+
Axx + B
2) (+ xy +
yz)dx =
(2xz -

Cy) dy 5
A =
B = -

t
( + xy + yz)dx +
(2y 2xz)dy
-
= 0

5 (** 53)
= -2y
c
scosy
-
-
=

y =((ux
-
(n(x +
3)) -

3 cosy
= 2
IF :

+x-2y +
-) =

y(+x y) + C =

y · In) 3) -

3 cosy

an 2(x+ y)

/y 5 (T-yyz]dy
=
= + = 0
y((x
+
y) ty2

(( +xy yz)dx (2y 2xz)dy 0]


GM ()
+ + -
=

= u =
x +
y

-
-
= -

-n ((y)
[xyz)3/
EDE :
= -

c =

(2)-2x) +
Say
-Cyr))
+
y
(C =

my +
-
+
x)y(y =
x +
xy y(ny
+ x

3) (3x 2y3 y 2xz)dy () (ut)


*
+
+xy)dx + (3x + =
0 ; n =
x +
yz

= gy + a [xyz)3/ ~
= -
IF
: SP(y) ebJydy-

EDE
=

j xe2 =
Jesing dy ; IBP :
Sudu
n = e2y
=
ur-Jrdu
av =

singly
du =
ze3Y dy v
cosy
= -

5) e-cosy- (-h/cosyey dy))


Stanto x = tano 28
-
=

20s
+
yz Sudu =
ur-Jrdu
u e2Y dy

S20
=
av =

cosy
= secoce =
Instant du =

2e3Ydy v =

siny
Jesinydy -ecosy-[-2(esiny- 2Seysinydy)]
=

Fre x (n(x + 1xyz) + +


my =
C
=
=

ecosy + 2e %sing -
+
Jesinydy
Seysinydy -ecosy 2e24siny=
+

1 5

+)222 siny encosy)


< -

Y
Linear DE (3) (5) [xe =
-
5
+
2]
e2Y /Isiny cosy)
<
15 xe y = -
+ C

1 .

) (xy +
1)dx -

(1 xz)dy -
= 0

4)(2x y)dx xdy + - =


0

(xy +
1) -

x)dy = 0

(1 -

x4) dX
(2x y)ax xdy + - =
0

X dX

& )y = -
2
- Y
t
Y
-

a =
0 - +
( x)y =

7
-
X

IF
: SP(x) eS -[in(x2 1) IF
(P(x) e
:
- -

=
e =
= ex
yum =

-Jax = * =

ef =
-
+ C

Y1 +
= arcsin(x) + C x (* = -

x + c)
CX 2
y
= -

2)) y)dx
*
(x -
3x -

X
dy
=
0 ; y(z)
=
2

(x)) +
-

(x -
3x
y)dx
- -

X
3

dy
=
0 5) <y - esin x =
0
; y()
= 0

3
dx
(y - esin (x))
-
X -

- + x =
0

* -

- =
0 - +
()y =

*
Tay
-
IF

: SP(X)S *
X-
- + ()y =
yx =

fxdx fx =
dx =
+x + c
IF :
Jp(x) SF
dX
sin"(x)
Cy(1) = 2 1 x2 -

je Sen
C
= =
C
sin-(x)
(2)(1)3 =
+(1) 2 + - c = sin()
dX
u =
2

in
;
=

3(yx =

-
5)
+x + -
3 Cy(0) = 0
du
= y

3yx3 =
x3 + 5 late
sin" ( 00
= -
asint( -
e

3 .

) 3dx +
(6xy siny) dy
- =
0 c =
-
2 yesint(x) sin(x
3dx (oxy-siny on
=

- + =
· -2 d
ve =

ve = -
x + C ; gv =

(1 + x2) ( eX
= -
x + c) yet
ye" (c )
*

1 x
-

+ jy
1
=

-
--
1 + x2

2)(y 2xy)dx 3x dy
+
- + = 0
If :

eSP(x) x)ax
eS / x2 + 1)
1
= =
-
l
2xy) +x -
3x2dy
- + = 0

3x2d
Y(x +1 =

f -
[+=
)y
y
&Y
-
-
t
=

yum
2
=
(nx + C X

Substitution :

+ v =
y
3

2) x
dy
-

sin(2x/dx + 3xydx = 0
dV t dy
3* () v - ) Bay
-

+ =
- =
-
3y
-

d
-
x
dy
-

sin(2x/ *
x +
3xyx = 0

dx x2

dy -
(2x
sin
sin & ()v + =

Y ;
IF
:SP(x) z 24x
a
-

Xa
+ =
0
- y
=
= 2

(dx
3
ev
-

vx2 = =
x + c ; =

y
esP(x)3
IF :

y3 = x + c)x =

y(x +
yx3 =

Sxsin(2x)dx
3)
IBP :
Sudu = ur-
fudu
sin(2x)dX
[a (*)y )-
*(y]y COS
u =
Xdv =
+ =

X3
du =
dX v = -

Ecos(2x) substitution

Sxsin(2x) = -

* Xcos(2x) -

( (cos(2x)ax)
-
+ - =x v =

y
-
2

2 (*)v = y
3

[-( sin(2x))]
-

+
-
-
=

(yx" &sin(2x) Excos(2x) c) & (


x

: (P(x) =
COS
4) + It
= -

+ = -

2 /

Y3

tyx" =
sin(2x) -

2xcos(2x) + C
vxt = -

2) xoxox =
-2(xsin(x) + cos(x)
- 2
2v y
Bernoulli DE
=

j2 E -
X
2[xsin(x) + cos(x) +
c]]
T
- -

-) dy +
ydx =

2xy - edx
x =

2y2 (xsinx + cosx +


c)
2xy ex dx
-

dX
dy + -
2xy ex
=

y
-

y
>
-
+ =

dX
4) (j(5(x -
2) -

-j]dx (x 2)dy - - =
0

( +
y
=
Exe)y > -
+
y = 2xex
-j(5(x -
2) -

-j]( (x
- 2)dy
- - =
0

Substitution : (x 2) - dx

+
-

( + v =
axex)
[iz)]y-
=
y [5(x 2)]y
=
v
0
- -
=

( -v -2xex
k( (x2)y 2)]yk)
-

y + =
(5(x -

-
IF :

Sdx
eSP(x) + (2)v 5(x
-

x =
=
e =
e
Substitution :

v =
+ ( 5(x -
ye
=

= ) = t
-

2) ↑

: SP(X)
IF 1
Em(x -

2
=
-

5)(x 2)3/ dx
=
-
x 2 -
= -
=
(x 2) -
+ c

gu ye =

*
↓ y(x
-

2) =
(x 2) -
+ c

5
.

) -
xcot (2y) =

xcs (zy)

(x-xcot (2y) =
xcs(2y)] x

+ (cot(2y)] =
cx(2y)
Substitution :

v =
x
- 2 -

2) +
[ ct (2y)]v =

cs(zy)
- = x a +
2c0t(2y)v = -

2cx(2y)

IF
/ sin (2y) /
:

(JP(y) = - 2 (cot(2y)dy =
-
e

~
sin(ey)
= -

eSydy =
z
2
2
-

v =
x

&
sin (2y
[ c] sin(2y) (C 2y)
=
X2 2y
+
-
=
=
x
-

-
Xz
HLDECC (m )2(m +)(m + 1)(m2 + f)
=
r
+ -
=
0

1) (D +Di 5D)y
+
+ +Do + +D -
-
=
0 Roots :

m 4
Aux
= -

: z
,

715 m7 + +mb + + m5 -

+m
+
-
5m" = 0 M3 , 4 =
12
↑ =

q 11 1
m3 (m + mj =

4m3
-

=
+ + +m -
4m -

5) =
0

M617 = Li

5 -
1 I + +
- -

159 5
+X(( (x)
*

56
* x
2xe (+ e
-

=
e + + + + (e
15 9 y
+
Cocos(2x) + C = sin(2x)
-
5)1 ↑ 5
-
5 -

- 3) (D" 2D" 4D" 2)y


-

11 g -

D - + -
5D + 5D - =
0

Anx
Roots : : ma
-

2mY1 - 4m" -
5 m2 + 5m -
2 =
0
M - -

m3(m 1)2(m +
1)(m 5) + 0

&
-
=

M = 0
, 2, 3
11 1 2 + 4 5 + 5 2
- - - -

10 22 3 2
1
-
-
= -

My , 5
-
ma
=
1 20
1 -
22 -
21 O
m 5

-
= -

y
=
G 22x
+

+ (x + e "((p (5x) +

+
Coex + Ge5x
m2 + 1 = 0

16D (n
2)(D Di + 4D" F1
+
+
+ + +D
-
=
= =
= i

64)y Roots :
-

16D" -

b+D - =
0

1
Aux m, , 2, 3 = -

m =
2
+
m
+
+ my + + m5 + +m -
16m3 -
16m
2
-
64m -

64 =
0
+

M5, 6 = I

&
=
1 =2 = 418 1
I 1
16 = 32

y
= e X (G + (2x +
(3x2) +
C + e2x + ((cos(x)
+ Cosin(x)]
)1 1 4 + 16 16 64 64
- - -
- -

64
+
10 40160
y
- -

4) 0 ;
=

3 X

10 T - y'(0) = -
3 ,
y"(0) = 1

- -

O
Aux :

m3 -
m2 + +m
-
+ = 0
Roots

m,
:

= 1

M

+ 0m3
- + 8 m2 + On + 16
m2 (m 1) +(m- + -

1) =
0 m2 , 3
= 12i
2
+ 2
+ 8m + 16 ; let u =
m
(mz )(m 1)
m
+
+ - =
0

u2 + 8u + 16
-2 F+ = = z2i
-
8 = ((8) 2
-
+(7)(1b)"
U1 z
= =
-

4 G , e" ((zcs(2x) +
Casin(2x)]
y
= +
,
2(1)

n = -
+ ; substitute back
y
=
(ex
I
-

2Czsin(2x) +
2Cycos(2x)
-
m2 F+ = = 12i y" =
C eX -
↑ (2cos(2x) -

↑(ssin(2x)
& y(0) = 1
, y'(0) = -
3 ,
y"(0) =
1
ya =
G +
2x +
Cze

1 =
Ge --
C2cos(2(0)) Conecoss" + +
Yp :

1 =
G +
Cz Yp ,
=

Ax
+
+ Bx3 + 2x
-
; Ypz =
Dxe

- -
"

C,
*
-
3 = -

2Csin(2(0)) + 2Cycos(2(0) Yp = +Ax + 3Bx2 + 2(X ; Ypz = De (2x + 1)


-
3 =
G +
2(z y"p =
12AX2 + 6Bx + 2 ; Y"pc =
+De2X(x + 1)

1 =
Ge14C201)" -

-
↑Casin(2(0)) y "p =
2+ Ax + GB ; Y"pz =
+ De 2X(2x + 3)

1 =
4 -

TC 2+ Ax + GB -

2((2Axi + 6Bx +
22) =
1 -
x + e2x

↑ De 2x(2x + 3) -

2[+ De2X(x 1)] + =


1 -
x + e2x
2, =
1

ex 2sin(2x)
C y Equating Coefficients
=
=
0 :
-

2
23
=
=
-

X 2: -
24A = -

1 A

X' 24A 12B 0


=T
NHLDECC
:
B
-
=

X" : GB -
+C = 1 c = -

to
-) (D* D2)y -
=
x
-
eX
ex : 12D 8D 1 D =
-
=

Ye :

-x e
m -
m2 = 0 m
,z
=
0
Yp
= +
- -
+
&
2
(m =
1) 0my ,+ = T

-xe2X
m -
= =

y =
G +
2x +
Cze +

Yc
=
G +
2x + Cze + GeY
2x

Yp :
2) (D3 -
D2 + +D -

+
)y =
e + cos(2x) -
Csin(2x)

Yp .
=
Ax3 + BX2 ; Ypz = CxeY Yc :

m3 -
m2 + +m -

+ =
0m , 1
Ay
=

Yp =
+ Bx + (xeY

3Axi CeY(x + 1)
m2 (m 1) -
+ +(m 1) - =
0
m23 12i
yp
=
=
+ 2Bx +

y "p bAx + 2B CeY(X + 2) Yc Gex Cecos(2x) Csin(2x)


=
=
+ + +

y "p =
GA + CeY(x + 3) Yp :

(x + 4)
+

y""p =
ce
-2x
Ypz =
Axsin(2x) + Bxcos(2x)
Yp .
=
Ae ~
Ce"(x + +) -

GAX -
2B -
Ce (x +2) =
x
-
ex yps
=
Axsin(2x) + Bxcos(2x)

Equating Coefficients
:
y "p :

ex = +C -
2C = -

1C = -

- Yp = -

2Ae-ex

x :
-
GA =
1 A = -

4 y"p ,
=
&Ae-2x

Yp
= -

y +
OXXe
--- Y"p ,
= -
Ste-2x

[2xcos(2x) sin(2x)] + B[ 2xsin(2x) cos(2x)]


- YP2
" = A + -
+

y
=
G +
(2x + Cze + (ex ,
3

Y"P2 3 ,
=
A[- Pysin(2x) + s(2x) +
20(2x)] + B[ -

TXcos(2x)

2) (D2 2D2)y -
=
1 -
x + e2x -

2si2x) zitax)] -

Ya : =
A [-txsin(2x) + 4cs(2x)] + B[ 4xcos(2x) Psin(2x)] -
-

m3 - 2m = 0 m
, z
= 0 Y"p2, 3
=
A [-oxcos(2x) (ix) - -
(2x) + B(8xsin(2x) -

m2 (m 2) -
=
0mz =
2
40(2x) 8c(2x)]
-

=
A( -

Excos(2x) -
12 sin(2x)] + B(xsin(2x) 12cos(2x)] -
&( Excos(2x) - -
12 sin(2x)] + B(8xsin(2x) -

12cos(2x)]3- -
e
2x
So
-

=
((x -

x + 2)
[A( xsin(2x) + + 4cos(2x)) + B( -
+ xcos(2x) -
Psin(2x)] 3 +
0
=
x2 -

(n(x) + 2x

↑ [A[2xcos(2x) + sin(2x)] + B[ 2xsin(2x) -


+
cos(2x)]] -

Sp =
(5 x(x * 2]3
-
-

4 [Axsin(2x) Bxcos(2x)] + = cos(2x) -


Csin(2x) p = -

) x x + -

Expanding :

2x(G x x((x) xz)


-

(2x + + x +
y
=
e + -

12 Bcos(2x) +
-
os(2x) -
RAsin(2x) Bysin(2x) Asin(2x)
-
-
+

tAcos(2x) +
xcos(2x) + + Bsin(2x) + Axcos(2x) + Asin(2x)

Bysin(2x) ↑ Bcos(2x) Exos(2x)


= + -

#Axsin(ix) -

=
cos(2x) -
Isin(2x)

Simplifying :

8Asin(2x) -

8Bcos(2x) -

↑Acos(2x) + ↑Bsin(2x)
=
cos(2x) -
Isin(2x)

Equating Coefficients :

sin(2x) :
-
8A + +B = -

2A =
cos(2x) : -

8B -

+A =
1 B
=
-
For e-2x :

8Ae-2 ↑Ae-2X-8Ae2x-4Ae-2X
*
-
- =
e-2x
2x
24Ae-2x
-
-

=
e
-

24

-
2X
-(2x)
3xsin (2x)
Tt
XCOS
Yp =

20
- -

5
-

(sin(2x) t x(2x)
3
y =
Ge" + Cecos(2x) +
20

xs(2x)-

1) (D2 +)y 2x(x y 2)


-

+
+D +
-

+ =
e

Ye :

2
m + +m + + = 0

M1 , 2- = -
2

(m + 2) =
0

(4 (x)
-

yc =
e +

Yp :

Yp 2x(p 0x)
-

=
e +

Y'p 2x(( (x) ze (p 0x)


-

0
=
e + + -
+

y "p 2x(0
:
40 2p' 44 28(x 40x)
-
- - -
+
e
-
=
.

2x(0
:
2p' 28(x +0x) 4[e 20
-

48 4p
-
- - -
+ +
e
-

je (p 0x)] (e 2x(P OX)] 2x(x y 2)


-

+ +
+
-
-

+ + =
e

[p + 0x =
03
LAPLACE DE
#
1) y"(t) y(t) +et ; y(0) 1 y'(0)
+ = =
,
=
3

G(y"(t)3 GGy(t)) + GGe 3 + =


+

[02y(s) [50)" -
+
Mp3 [5Y(s)-Noi] = +

say(s) + =
+ sY(s) X - =

-
1
+ 5


57(s2 s)+
<y
+ +
-1

+
c -

13 +
= E
PFD :

es =
0

1 =
A(b + 1)(8 1) -
+
B1) + co
+ 1)
-

A
-
=
1

es

1
=

1 =
A(x + 1)(b 1) -
+ -
By(b 1) + (s(b + 1)
-

c =

4
Es =
--

1 =
-
A(s1 + 1)(5 1)
-
-
+ B- 3 (s 1)
-

+
-1) +

B =


[d +
PFD :

es = 0

1 =
A(g + 1) +
A =
1

es 1
-
=

1 =

A1) + + B 5)-

B = -

5
[13: 23
y(t)
=
f
+ + Ge
+
+ Le
+
5
+ -

5e
t

+
=
Isint -

je + 1
00

ANGELO LOUISE OLARTE


BSIE 2A

ACTIVITY NOTEBOOK
In Partial fulfillment for the completion of the course
ESM 2034 (5-929)

Submitted to:
Engr. Ottoman Montani Jr.

You might also like